Compact dynatron modulator - Agafonov, A.V. (Вопросы атомной науки и техники, 2001)
It is proposed to use a dynatron effect to modulate the voltage across the vacuum inverted coaxial diode with magnetic insulation supplied by an external pulsed high-voltage source connected to the modulator via the RL-circuit. Oscillations of the voltage due to oscillating regime of diode charging and/or azimuthal instability of a rotating electron flow stimulates back-bombardment electron flow to the cathode and leads to power spikes of secondary emission current exceeding the primary one. As a result, the amplitude of oscillations grows and the system can turn to self-supporting regime. Results of computer simulations are given to illustrate the main physical processes inside the modulator and its possible applications.